Designing a Health Bathroom with Central Asian Bathroom Traditions (Architecture-Construction Part) - Melikov Zarshed Jamshedovich (Research Parks Publishing LLC, 2021)
The article, examines the design of a modern energy efficient building that meets international standards. In the section of architecture and construction, first of all, the master plan of the projected building is drawn up. Because the building building must meet the QMQ requirements. The climate of Urgut was studied and the wind directions were determined. The city of Urgut is located in the II zone. Zone II covers mountain oases, valleys, lands with good climatic conditions, beautiful flat mountains. Therefore, a design solution was developed that fully took into account the external environmental conditions (plants, gardens and orchards, ponds, calm air of mountains and valleys), and also took into account the main directions of local winds.